Doses e modos de aplicação de boro na produção de mudas de nespereira - Penha, Estevan Teodoro Santana [UNESP] (2016)
The loquat cultivation is increasing in Brazil and in the world and is an important source of income for small farms, however, the production of seedlings can be an obstacle to its expansion. Thus the aim of this study was to evaluate Boron reflection on the quality of loquat seedlings, and the place of supply to plants parent by determining the most effective application method in this process. There were four boron doses (0, 2.5, 5.0 and 7.5 mg dm-3) and two application sites (soil and leaf). The use of boron instock plants improves the root system of plants from cuttings, the most efficient foliar application than the soil. The application of this micronutrient promotes balance between root / shoot, ensuring the formation of a balanced changes, given that the leaf supply increases the volume of the stake roots. Therefore the supply of boron to headquarters makes the process effectively, reducing cost, optimizing time and assuring the quality of fruit seedlings.